HAK KEKAYAAN INTELEKTUAL (HKI) SEBAGAI OBJEK WAQAF DALAM HUKUM ISLAM - Inas Khairunnisa (IQTISHADUNA, 2019)
Embodiment of the Benefits of Intellectual Property Rights for community problems, one of which is through waqf. This paper is proposed to answer the question about the position and basis of Intellectual Property Rights (IPR) as one of the waqf objects as stipulated in article 16 paragraph (3) of Law (Law) No. 41 of 2004 concerning Waqf, so the object of IPR waqf is possible in this modern era. Literature research type writing uses normative juridical research. The results obtained from endowments use IPR as its object, is permissible (legitimate) based on the opinion of Malikiyah scholars. Even so, the HKI that is represented may not be violated by the provisions of the Shari'ah.